2004
DOI: 10.1037/0021-843x.113.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions About Schizophrenia in Families in China: Expressed Emotion and Patient Relapse.

Abstract: Previous studies have indicated a robust link between relatives' causal attributions and levels of expressed emotion (EE). However, these studies have primarily been conducted in Western cultures. The current study, conducted in China, examined the spontaneous causal attributions made by 54 relatives of schizophrenia patients during the Camberwell Family Interview. Chinese relatives made few controllable and personal attributions overall. Yet as predicted, highly critical and/or hostile EE relatives attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
0
40
0
1
Order By: Relevance
“…This can be explained by the relatives ' causal attributions about the negative behaviours manifested by people in recovery from schizophrenia. Only those critical relatives who viewed challenging behaviours as personal and controllable were predictive of relapse among individuals with schizophrenia (Yang et al, 2004). If relatives had a more benign or social explanation of challenging behaviour they were more likely to show support and concern.…”
Section: Moving Forwardmentioning
confidence: 96%
See 1 more Smart Citation
“…This can be explained by the relatives ' causal attributions about the negative behaviours manifested by people in recovery from schizophrenia. Only those critical relatives who viewed challenging behaviours as personal and controllable were predictive of relapse among individuals with schizophrenia (Yang et al, 2004). If relatives had a more benign or social explanation of challenging behaviour they were more likely to show support and concern.…”
Section: Moving Forwardmentioning
confidence: 96%
“…Previous studies in Hong Kong and mainland China (Ng et al, 2001;Ran et al, 2003b;Yang et al, 2004) have found that high expressed emotion in the form of over-criticism and hostility among family members was predictive of relapse among individuals with schizophrenia. However, moderate levels of overprotectiveness were found not to be predictive (Ng et al, 2001).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Numerous factors were responsible for lack of seeking help for overcoming addiction among substance users [75 ]. Other studies have looked at causal attributions from schizophrenia in families in China [76] and 10-year treatment outcome in traumatized Cambodian refugees [77 ]. A review [78 ] of the home treatment services showed that more than half of the efforts did not go beyond the trial period and the continuation of the treatment program depended on the benefits in decreasing hospitalization.…”
Section: Health Services Researchmentioning
confidence: 97%
“…This population was also selected because of the unexplained worse disability and symptomatic outcomes for schizophrenia in Chinese-speaking native populations (Ran et al 2001 ;Hopper et al 2007 ;Cohen et al 2008). While we have previously examined psychosocial factors impacting course (Yang et al 2004(Yang et al , 2008(Yang et al , 2010, the present study investigates a novel mechanism -an interaction between neuropsychology and languagewhich might account for poorer social functioning.…”
Section: Introductionmentioning
confidence: 99%